ANTI DIABETIC FLAVANONE COMPOUND FROM THE LEAVES OF Artocarpus communis - Puspa D.N. Lotulung; Sofa Fajriah; Andini Sundowo; Euis Filaila (Universitas Gadjah Mada, 2009)
The Flavanone compound with anti diabetic activity was isolated from ethyl acetate extract of Artocarpus communis leaves using column chromatography techniques. The structure of the flavanone compound was elucidated on the basic of spectroscopic evidence and comparison to published values. This compound, 8-geranyl-4,5,7-trihydroxyflavone, showed strong anti diabetic activity on α-glucosidase inhibition assay with IC50 18.120 µg mL-1.